Rethinking agricultural policy regimes food security, climate change and the future resilience of global agriculture - Almås, Reidar, 1943-; Campbell, Hugh, 1964- (Bingley, U.K. : Emerald, 2012)
For many decades debates about the future of developed world agriculture policy have been dominated by a long political conflict between European/multifunctional policy regimes and the global trend towards trade liberalisation. The stalemate that had emerged between these two positions by 2000 has now been dramatically reconfigured. This book argues that there are four reasons why this area of policy has now reopened to wider debate: The World Food Crisis of 2008-2011 has signalled a potential end to the era of cheap food. The emergence of climate change as a core policy concern has shifted key targets for agricultural policy. New trends towards 'neo-productivist' agricultural policy have emerged to challenge multifunctional approaches to agriculture. New academic ideas around resilience of food chains and relevant policy interventions have challenged established approaches to achieving agricultural sustainability. Through international case studies, this book evaluates how these new policy challenges are having an impact on specific agricultural policy regimes, and what future lessons might be learnt from key policy experiments around neoliberalism and multifunctionality.
Introduction : emerging challenges, new policy frameworks and the resilience of agriculture / Reidar Almås, Hugh Campbell -- The evolution of Western agricultural policy since 1945 / Bruce Muirhead, Reidar Almås -- The rejuvenation of productivist agriculture : the case for "cooperative neo-productivism" / Rob J.F. Burton, Geoff A. Wilson -- Western European approaches to and interpretations of multifunctional agriculture and some implications of a possible neo-productivist turn / Katrina Rønningen, Alan Renwick, Rob Burton -- Food regime crisis and revaluing the agrarian question / Philip McMichael -- The food crisis and the changing nature of Scottish agricultural policy discourse / Andrew Midgley, Alan Renwick -- The worlds of dairy : comparing dairy frameworks in Canada and New Zealand in light of future shocks to food systems / Bruce Muirhead, Hugh Campbell -- Norwegian dairy industry : a case of super-regulated co-operativism / Reidar Almås, Jostein Brobakk -- The complex outcomes of neoliberalisation in New Zealand : productivism, audit and the challenge of future energy and climate shocks / Christopher Rosin, Hugh Campbell -- Emerging neo-productivist agriculture as an approach to food security and climate change in Norway / Hilde Bjørkhaug, Reidar Almås, Jostein Brobakk -- Comparison of bioenergy policies in Denmark and Germany / Gerald Schwarz, Egon Noe, Volker Saggau -- Commodity competition : divergent trajectories in New Zealand pastoral farming / Paul Stock, Susan Peoples -- Reframing policy regimes and the future resilience of global agriculture / Reidar Almås, Hugh Campbell.
Print version record
Keywords: Social Science -- Sociology -- Rural; Social Science -- Agriculture & Food; Social Science -- General; Sociology; Rural planning; Agriculture and state; Agriculture